Group classification of systems of nonlinear reaction-diffusion equations with triangular diffusion matrix - Nikitin, A.G. (Український математичний журнал, 2007)
Group classification of systems of two coupled nonlinear reaction-diffusion equations with a general diffusion matrix started in previous author’s works completed in present paper where all nonequivalent equations with triangular diffusion matrix are classified. In addition, symmetries of diffusion systems with nilpotent diffusion matrix and additional first order derivative terms are described.